2006
DOI: 10.1007/s11032-006-9029-y
|View full text |Cite
|
Sign up to set email alerts
|

High glucosinolate broccoli: a delivery system for sulforaphane

Abstract: The development of hybrid broccoli genotypes with enhanced levels of 4-methylsulphinylbutyl glucosinolate, the precursor of anticarcinogenic isothiocyanate sulforaphane (SF), by introgressing genomic segments from the wild ancestor Brassica villosa is described. We demonstrate that to obtain enhanced levels of either 3-methylsulphinylpropyl or 4-methylsulphinylbutyl glucosinolate it is necessary to have B. villosa alleles in either a homozygous or heterozygous state at a single quantitative trait locus (QTL) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…The underlying genes are likely to correspond directly to cloned genes that have been functionally analysed in Arabidopsis, described above. In addition, quantitative trait loci (QTLs) have been identified that determine the overall level of GLSs in both B. napus [59,60] and B. oleracea [61,62]. The genetic regulation of indolyl glucoisnolates derived from tryptophan is far less advanced.…”
Section: Breeding For Altered Gls Content In Brassicamentioning
confidence: 99%
“…The underlying genes are likely to correspond directly to cloned genes that have been functionally analysed in Arabidopsis, described above. In addition, quantitative trait loci (QTLs) have been identified that determine the overall level of GLSs in both B. napus [59,60] and B. oleracea [61,62]. The genetic regulation of indolyl glucoisnolates derived from tryptophan is far less advanced.…”
Section: Breeding For Altered Gls Content In Brassicamentioning
confidence: 99%
“…Different members of this family may catalyze different number of rounds of elongation, with genetic variation at the GS-ELONG and GS-PRO loci enabling selection for different glucosinolate profiles, while allelic variation at the quantitative trait loci determines overall amount (286). These initiating factors have been observed in both Arabidopsis and Brassica (58,242). In B. oleracea, these genes determine the length of the side chain with either one or two rounds of methionine elongation to produce 3C or 4C glucosinolates, respectively (242).…”
Section: Introductionmentioning
confidence: 99%
“…If the glucosinolate side chain contains a double bond (alkene) in the chemical structure, in the presence of epithiospecifer protein (ESP) and ferrous ions, the thiohydroximate rearranges to produce an ETN and nitrile (Bones and Rossiter 2006). ESP is more sensitive to thermal processing than myrosinase and short periods of steaming can alter degradation profiles to increase ITCs with a marked reduction in nitriles and ETNs (Sarikamis et al 2006). Thus ETNs and nitriles are more likely to be formed in raw vegetables (Abd Kadir 2013;Kyung et al 1995) such as in salads where for example cabbage is used.…”
Section: Introductionmentioning
confidence: 99%